Unforgettable: History, Memory, and the Vichy Syndrome - Rosemarie Scullion (Studies in 20th & 21st Century Literature, 1999)
In 1987, the French historian Henry Rousso formulated an interpretive model that has decisively influenced the directions and forms of inquiry scholars have pursued in relation to les années noires, the period between 1940 and 1944 during which France endured a catastrophic military defeat and four years of occupation by a neighboring fascist state...
Keywords: 1987; French historian; Henry Rousso; les années noires; military; occupation; France; French; World War II; Second World War; Vichy Syndrome